The contribution of VSA and SDL perspectives to strategic thinking in emerging economies. Issue 6 (4th November 2014) - Pels, Jaqueline; Barile, Sergio; Saviano, Marialuisa; Polese, Francesco; Carrubbo, Luca
Abstract : Purpose: – The purpose of this paper is to reflect upon strategic marketing in emerging economies (EEs). It tries to answer the research question: what new business models are enabled by the Viable Systems Approach (VSA) and Service-Dominant Logic (SDL) perspectives? Design/methodology/approach: – The paper is developed by integrating two well-established perspectives – VSA and SDL – and applying them to inclusive businesses. Findings: – The integration of these perspectives allows the authors to recognize a convergence toward business models that seem to be consistent with the principles of inclusive capitalism. The authors claim that by shifting between a reductionist/static and a holistic/dynamic view, these perspectives can be integrated, thus revealing an interesting contribution to the understanding of inclusive business. Specifically, they contribute by highlighting how the economic and social dimensions are intertwined and by highlighting that the management-thinking perspective, which has dominated in recent decades, should shift toward a more inclusive vision. Research limitations/implications: – The paper represents an attempt to address an inclusive capitalism perspective in the context of marketing. Nevertheless, the conceptual reasoning developed in the paper should be further supported by empirical research carried out in the context of EEs. Practical implications: – The paper has relevant managerial implications that suggest a rethinking of the business model to market with EEs. Originality/value: – The paper contributes to the research on inclusive capitalism by linking it to well-grounded conceptual approaches to business that recapture a harmonious relationship between the economy and society.